Deconstructing and re-inventing the concept of multilingualism: A case study of the Mauritian sociolinguistic landscape - Tirvassen, Rada; Ramasawmy, Shalini Jagambal (Stellenbosch Papers in Linguistics Plus, 2017)
This article aims at deconstructing the conception of multilingualism developed in mainstream sociolinguistics by critically examining the assumptions underlying this trend of research, which is grounded in the scholarship of Labov, Fishman and even Gumperz. In order to embrace that discussion, the Mauritian sociolinguistic landscape, as described by researchers following that tradition, serves as a case. We, thus, set out by engaging in a meta-analysis of existing sociolinguistic research conducted in Mauritius. We critically discuss and reflect upon the assumptions underpinning such research, and in so doing, key concepts such as language and diglossia are challenged. This leads to the crux of the discussion about how such representations have impacted on the type of knowledge constructed about multilingualism in Mauritius. Finally, we open up a discussion on the need to adopt an alternative epistemological position in order to construct a different type of interpretation of the phenomenon following the ground-breaking work of scholars such as Makoni and Pennycook (2007), Herdina and Jessner (2002), Blackledge and Creese (2010), Garcia (2009) and de Robillard (2005 and 2007).